TELAAH PEMIKIRAN MAZHAB SYIAH DAN SEJARAH PERKEMBANGAN AL AZHAR DI MASA FATIMIYAH - Nisaul Hasanah; Haidar Fikri Khairunnida (Prodi Tasawuf dan Psikoterapi, Fakultas Agama Islam, Universitas Muhammadiyah Cirebon, 2021)
This article discusses the significance of the Shia school and its contribution to the Islamic treasures in the era of the Fatimid dynasty. This era is important to analyze considering that one of its contributions is the birth of a center of Islamic scholarship called Al-Azhar University (Egypt), one of the oldest and leading Islamic universities in the Islamic world until now and has become a place to gain knowledge from various parts of the world. in Egypt. The Shia group itself was formed because of people who gave fanatical support to Sayyidina Ali bin Abu Talib, the successor of Uthman bin Affan's caliph. The Shia group continued to grow and develop from age to age; from Caliph Ali to the Fatimid dynasty. The research method in this paper prioritizes literature review from library sources that discuss the role of Shia for Islamic civilization. In presenting the research results, this article uses a descriptive- analytical method. A number of findings in this research include: the contribution of Shia thinkers and figures in advancing Islamic scholarship and the role of Shia schools in creating a Muslim intellectual center, Al-Azhar University.